Designing an Interactive Flip-Mind Module on Temperature and Heat Concepts to Facilitate Critical Thinking-Oriented Learning - Intan, Wahyu Noor; Susilawati, Susilawati; Kusuma, Hamdan Hadi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2025)
Critical thinking skills are essential for students facing the challenges of the Industrial Revolution 4.0 era. This study aimed to develop and analyze the feasibility of the Flip-Mind interactive module, evaluate the improvement of critical thinking skills, and examine students' responses to its use on temperature and heat materials. This study employed a Research and Development (R&D) method, utilizing the 4D model (Define, Design, Develop, and Disseminate), integrating case-based learning and critical thinking components through interactive HTML5-based features to enhance conceptual understanding. This research employed a pretest-posttest control group design with purposive sampling involving grade XI students from a public senior high school. The validation results indicate that the module is in the "very feasible" category. The improvement in critical thinking skills was indicated by an N-Gain value of 62.7% (moderate category), with an average increase in score of 11%. Students' responses to the module’s use were in the "outstanding" category with a percentage of 82%. These findings suggest that the Flip-Mind interactive module is a practical and feasible alternative to innovative teaching materials for improving critical thinking skills in physics learning. Theoretically, this study enriches the framework of digital learning innovation by demonstrating the integration of case-based and critical thinking-oriented approaches. Practically, the Flip-Mind module offers an effective pedagogical model that can be adapted for interactive and student-centered physics instruction.